Culturally and Geographically Relevant Content in Secondary Physical Education: Lessons from the Greenbrier CHOICES Project. Issue 4 (4th May 2018) - Braga, Luciana; Elliott, Eloise
Abstract : This article discusses the concept of culturally and geographically relevant content and provides suggestions for its implementation in secondary physical education. The authors define culturally and geographically relevant content as that which is congruent with the contextual environment in which it is being taught and is determined by the students' background and interests, the physical environment surrounding them, and what resonates with their way of life. The suggestions for including culturally and geographically relevant content in a physical education curriculum discussed in this article are a result of lessons learned through the Greenbrier CHOICES project, a three-year multicomponent school-based initiative funded by a U.S. Department of Education Carol M. White Physical Education Grant and implemented in two middle schools in an Appalachian state.